Drivers of firm-government engagement for technology ventures - Lauren Lanahan; Iman Hemmatian; Amol M. Joshi; Evan E. Johnson (PLoS ONE, 2025)
Prior scholarship generally examines the returns generated by firm-government engagement. These studies are based on an implicit and understudied assumption – the firm’s strategic choice of whether to engage with the government. Here, we unpack the drivers of this choice. To do so, we construct a population-level sample of U.S. high-tech ventures founded between 2015–2017; the full sample exceeds one million firms. We then utilize government records to identify initial firm-government engagement; approximately 24,000 high-tech ventures reveal this preference by firm age three. We examine a range of external and internal factors that may motivate such a choice. The results indicate that firm-government engagement most prominently coincides with firm resource constraints. Features driving such engagement include: (i) underrepresented minority-owned firms; (ii) small firms; (iii) firms with greater early-stage growth potential; and (iv) firms located in less intensive entrepreneurial settings. This study offers managerial, policy, and scholarly contributions by uncovering new insights around firm strategy and government opportunities for high-tech ventures.